The role of structural and process quality of family planning Care in Modern Contraceptive use in Indonesia: a multilevel analysis - Nurjaeni Nurjaeni; Yothin Sawangdee; Umaporn Pattaravanich; Charamporn Holumyong; Aphichat Chamratrithirong (BMC, 2021)
Abstract Introduction Despite contraceptive behaviors are influenced by multiple and multilevel variables, studies on modern contraceptive use in Indonesia has concentrated on single-level and mostly individual and household variables, and less interest has been devoted to multilevel analysis that accounts for community and SDP characteristics that may affect woman's decision to use modern FP method. This study aimed to assess the role of structural and process quality of family planning care in modern contraceptive use among women in reproductive ages in Indonesia. Methods This study analyzed data from the 2016 PMA2020 survey of 10,210 women in 372 enumeration areas in Indonesia. The data were analyzed using categorical principal component analysis and multilevel mixed-effects logistic regression. Results The key variables for structural quality were number of contraceptive provided, SDP supports CHWs, available water and electricity, and skilled FP personnel, while the main factors for process quality were privacy of clients and provision of post-abortion service. There were significant differences across communities in how study variables associated with modern FP adoption. The finding shows the evidence of significant roles of structural and process quality FP care in modern contraceptive use. Moreover, women with high autonomy in FP decision, those who had free national/district health insurance, and those living in a community with higher proportion of women visited by CHW, had higher odds of modern contraceptive usage. Yet, women who live in a community with higher mean ideal number of children or greater proportion of women citing personal/husband/religion opposition to FP, had lower odds of modern contraceptive use than their counterparts. Conclusion Study findings suggest improvement in structural and process quality of FP care will yield substantial growths in modern contraceptive use. Moreover, FP workers should also address adverse cultural/traditional customs in community and should target communities where the demand for modern FP was degraded by opposing social beliefs and norms. There was significant variation across communities in how individual, household, community, and SDP factors affect modern FP practice, hence, context should be taken into consideration in the development of FP intervention and promotion programs.